Determinan Kepuasan Pelanggan Pada Produk Pertamina Lubricants - Berto Mulia Wibawa; Iwan Vanany; Fakhri Anggara (Faculty of Economic and Business, 2017)
Determinants of Customer Satisfaction at Pertamina's Lubricants ProductLubricant industry is one of the strategic industries in around the world. The potential of the lubricant industry in Indonesia grows rapidly along with the increasing demand and the number of a vehicle from year to year. This study aims to analyze factors that influencing customer satisfaction Pertamina Lubricants product and measure how far the customer satisfaction level of its product. This study observed eight categories of Pertamina Lubricants product, with quota sampling technique where each category of the product taken 30 samples, so the total number of the sample are 240 respondents. Multiple linear regression and customer satisfaction index were used in this study. The study finds brand popularity has the most significant effect on customer satisfaction, followed by price and durability. Customer satisfaction level stands at 78 percent, which means belongs in the satisfied category. Managerial implications of this study provide strategies for Pertamina Lubricants to improve their business performance and to increase the level of customer satisfactionDOI: 10.15408/ess.v7i1.4309